The 5-HT6 Receptors in the Ventrolateral Orbital Cortex Attenuate Allodynia in a Rodent Model of Neuropathic Pain - Zhang, Yuxiang; Yang, Jingsi; Yang, Xixi; Wu, Yanan; Liu, Junlin; Wang, Yangdong; Huo, Fuquan; Yan, Chunxia (Frontiers in Neuroscience, 2020)
Mechanical allodynia, characterized by a painful sensation induced by innocuous stimuli, is thought to be caused by disruption in pain-related regions. Identification and reversal of this pathologic neuroadaptation are therefore beneficial for clinical treatment. Previous evidence suggests that 5-HT6 receptors in the ventrolateral orbital cortex (VLO) are involved in neuropathic pain, but their function is poorly understood. The aim of the present study is to unveil the role of 5-HT6 receptors in the VLO and the underlying mechanisms in pain modulation. Here, by using the spared nerve injury (SNI) pain model, first, we report that 5-HT6 receptor protein decreased in the contralateral VLO compared with the ipsilateral VLO in rats with allodynia. Second, microinjection of the selective 5-HT6 receptor agonists EMD-386088 and WAY-208466 into the contralateral VLO consistently and significantly depressed allodynia. Third, microinjection of the selective antagonist SB-258585 blocked the agonist-induced anti-allodynic effect, while the antagonist applied alone to the VLO had no effect. Furthermore, the anti-nociceptive effect of EMD-386088 on neuropathic pain was prevented by the adenylate cyclase (AC) inhibitor SQ-22536, and protein kinase A (PKA) inhibitor H89, suggesting that AC/PKA signaling might underlie the antinociception of agonists. Finally, the 5-HT6 receptors were found to be colocalized with a glutamate transporter (EAAC1) by immunofluorescent staining, and the glutamate receptor antagonist kynurenic acid was found to completely block antinociception. These findings indicated that the antinociceptive effect of 5-HT6 receptor agonists might occur via interaction with the glutamatergic system. Altogether, the agonists activated 5-HT6 receptors present in the glutamatergic neurons in the VLO to facilitate the AC/PKA cascade, which subsequently might evoke glutamate release, thus depressing allodynia. These ﬁndings suggest a potential therapeutic role of 5-HT6 receptor agonists in treating neuropathic pain.